'Speak up, Speak out: Communities and the Cost of Living Crisis' (Concept: The Journal of Contemporary Community Education Practice Theory, 2023)
“Tackling child poverty is a national mission - it is not something the Scottish Government can do alone, and it takes all of us to deliver the change needed”  -  Nicola Sturgeon MSP, former first ministerThe current Poverty and Inequality Commission was created by the Child Poverty (Scotland) Act 2017.  MSPs of all parties voted unanimously for its creation, and the adoption of statutory targets to reduce child poverty. The Commission came fully into being in July 2019, when it replaced the previous, non-statutory, Commission in place between 2017 and 2019. The Commission are, in government parlance, an 'advisory non-departmental public body'.